Correction: Implantation of a functional TEMPO-hydrogel induces recovery from rat spinal cord transection through promoting nerve regeneration and protecting bladder tissue. (7th September 2022) - Zhang, Yu; Li, Liming; Mu, Jiafu; Chen, Jiachen; Feng, Shiqing; Gao, Jianqing
Abstract : Correction for 'Implantation of a functional TEMPO-hydrogel induces recovery from rat spinal cord transection through promoting nerve regeneration and protecting bladder tissue' by Yu Zhang et al., Biomater. Sci., 2020, 8, 1695–1701, ; https://doi.org/10.1039/C9BM01530B .